2002
DOI: 10.1080/02701367.2002.10609040
|View full text |Cite
|
Sign up to set email alerts
|

Self-Controlled Feedback: Does it Enhance Learning Because Performers Get Feedback When They Need It?

Abstract: This paper examines whether self-controlled feedback schedules enhance learning, because they are more tailored to the performers' needs than externally controlled feedback schedules. Participants practiced a sequential timing task. One group of learners (self-control) was provided with feedback whenever they requested it, whereas another group (yoked) had no influence on the feedback schedule. The self-control group showed learning benefits on a delayed transfer test. Questionnaire results revealed that self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

49
305
6
40

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 268 publications
(407 citation statements)
references
References 29 publications
(42 reference statements)
49
305
6
40
Order By: Relevance
“…This type of self-feedback has been used and implemented earlier in the Fabry-Perot laser diode system, 22 biological system to control complex motor task, 23 and learning. 24 Another variant of the self-feedback control is the paradigmatic Pyragas control technique 18 where an additional time-delayed version of the variable is used. In this paper, our goal is to study the effect of the self-feedback term on birhythmicity; we concentrate on the fact that how the self-feedback parameter d affects the birhythmic oscillation.…”
Section: B the Self-feedback Control Schemementioning
confidence: 99%
“…This type of self-feedback has been used and implemented earlier in the Fabry-Perot laser diode system, 22 biological system to control complex motor task, 23 and learning. 24 Another variant of the self-feedback control is the paradigmatic Pyragas control technique 18 where an additional time-delayed version of the variable is used. In this paper, our goal is to study the effect of the self-feedback term on birhythmicity; we concentrate on the fact that how the self-feedback parameter d affects the birhythmic oscillation.…”
Section: B the Self-feedback Control Schemementioning
confidence: 99%
“…The purpose of this procedure is to control for the amount and scheduling of feedback or whichever variable is under the learner' s control. Several studies found benefits of self-controlled feedback schedules [17][18][19] . Learning advantages have also been shown for other types of self-controlled practice, such as the self-controlled use of physical assistive devices 20,21 , or giving the learners the opportunity to decide when to watch a video model of a skilled performer 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Examining how motor skill learning can be enhanced in persons with DS is not only of theoretical interest, but may also have important practical implications for the lives of those affected by DS. Given the ostensibly powerful learning effects of self-controlled practice conditions -that provide learners with a certain degree of autonomy -seen in typical adults and children 17,31,32 , we wanted to examine whether similar learning advantages would be found in participants with DS. We predicted that self-controlled practice, in particular the ability to choose when to receive feedback, would result in more effective learning compared to a practice condition without this opportunity (yoked group).…”
Section: Introductionmentioning
confidence: 99%
“…Chiviacowsky et al 22) reported that the error rate of a self-controlled group in a key push task on a computer key-board decreased more than that of a yoked feedback group. In addition, Wulf et al 24) indicated that acquisition of ski movement in a self-controlled feedback group was better than that in a yoked feedback group in motor learning on a ski simulator.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that training protocols incorporating some forms of self-control can be effective in motor skill learning 22,23) . In studies of self-controlled feedback, learners decide when they want to receive feedback about their movement in a motor task.…”
Section: Introductionmentioning
confidence: 99%